Clinical evaluation of resin infiltration treatment masking effect on hypomineralised enamel surfaces - Halenur Altan; Rabia Erağca Yilmaz (BMC, 2023)
Abstract Background Resin infiltration is a micro-invasive treatment for molar incisor hypomineralisation (MIH). In this study it was aimed to evaluate the masking effect of resin infiltration treatment (ICON) on hypomineralised enamel surface of permanent anterior teeth by using laser fluorescence, spectrophotometer, and cross-polarisation photography. Methods A total of 116 permanent central incisors in 37 patients were included in the study. The resin infiltration treatment (Icon®) was applied to the teeth with MIH; the healthy teeth received no treatment (control). Hypomineralised enamel lesions were evaluated by ICDAS II criteria. DIAGNOdent Pen was used to assess the lesions and healthy enamel surface quantitatively. Colour changes in enamel lesions were evaluated by using a spectrophotometer (VITA EasyShare). Each enamel lesion was imaged using a cross-polarization technique before and after treatment. All photos were assessed using Image J to evaluate the changes in lesion size. Enamel lesions were evaluated before; immediately after; 1; 3; and 6 months after treatment. Statistical significance was set as p < 0.05. Results After the resin infiltration, significant decreases were found in the mean DIAGNOdent values for the treatment group (p < 0.05). The colour differences before and after treatment significantly differed in all follow-ups (p < 0.05). In the treatment group, lesion areas decreased significantly after treatment (p < 0.05). Conclusions The resin infiltration treatment has a masking effect on MIH lesions without cavities, with stable outcomes after six months. The cross-polarization photography technique may be use to evaluate the lesion size instead of photography with flash. Trial registration. NCT04685889 (registered 28 December 2020).